PENDAMPINGAN ORANG TUA UNTUK MENSTIMULUS BELAJAR ANAK DISLEKSIA - Novita Sari Hsb (Jurnal Anifa: Studi Gender dan Anak, 2021)
Dyslexia is a disorder in certain parts of the brain that causes learning disorders in sufferers. Dyslexia is usually characterized by difficulties in language, understanding words or sentences, both in reading, spelling, and writing. Dyslexia is not a disability, it is just that children with dyslexia are different in the function of certain parts of the brain and have different learning styles than other children in general. Therefore, special handling is needed to overcome difficulties in learning to read in children with dyslexia. One method that can be used by educators and parents to overcome difficulties in learning to read in dyslexic children is by developing learning media. This study aims to develop digital literacy media for dyslexia of children to a concrete operational age. This study uses a research and development method by applying the ADDIE model. This model consists of five steps, that is analysis, design, development, implementation, and evaluation. The development of digital literacy media is expected to be effective in overcoming difficulties in learning reading dyslexia of children.